Industrial Potentials of Saccharomyces cerevisiae (British Journal of Multidisciplinary and Advanced Studies, 2023)
Saccharomyces cerevisiae has attracted much technological concern in recent times, owing to their extensive used in food manufacturing, fermented beverages like wine or beer and in promoting the development of industrial biobased products. Saccharomyces cerevisiae also known as yeast are eukaryotic organisms found in a wide ecological niches such as soil, water, air, plants, fruits and plant saps. Saccharomyces cerevisiae strains is the most common yeast known in history for their fermentative ability and are today biotechnologically compliance for industrial production of many products such as ethanol, yoghurt, Cheese, bread, wine and other alcoholic beverages. From their natural habitat, they have been successfully isolated and evaluated for their metabolic and fermentative activities. Investigations by many authors have shown that yeasts can be isolated from palm sap or juices, passion fruit, water melon and pineapple where they colonized as their natural habitats. The isolates from these habitats have also been evaluated and found to have attributes essential for industrial and commercial purposes. The attributes investigated include ethanol production, yoghurt, Cheese, leavening ability for bread making and other dairy products. Besides the aforementioned, yeast are used in the global food processing and manufacturing.  They are said to impart improvement in food quality, taste, texture, flavour and nutritive values. In this chapter, I elucidate the potentials of Saccharomyces cerevisiae strains with reference to their industrial and commercial uses. Their classification, cultivation and selection are also discussed.